2008
DOI: 10.1111/j.1399-3054.2007.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyphenol oxidase changes induced by desiccation of Ramonda serbica leaves

Abstract: Resurrection plants are able to dehydrate/rehydrate rapidly without cell damage by a mechanism, the understanding of which may be of ecological importance in the adaptation of crop plants to dry conditions. The o-diphenol oxidase in Ramonda serbica Pan. & Petrov, a rare resurrection plant of the Balkan Peninsula, was characterized in respect to different isoforms, preferable substrates and specific inhibitors. Two anionic isoforms with pI 4.6 and 4.7 were separated from turgid leaves. Three additional anionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 54 publications
(65 reference statements)
1
27
0
5
Order By: Relevance
“…Many studies have confirmed that antioxidants such as SOD and POD were shown to have increased in response to desiccation [40,41], and may act as a "reservoir" and determine the period where a plant can remain desiccated before its viability is compromised [42]. During desiccation, the SOD and POD activity of G. biloba seed embryos were first reduced, then elevated to the highest value, before declining.…”
Section: Changes Of Sod and Pod Activity In G Biloba Seeds During Dementioning
confidence: 99%
“…Many studies have confirmed that antioxidants such as SOD and POD were shown to have increased in response to desiccation [40,41], and may act as a "reservoir" and determine the period where a plant can remain desiccated before its viability is compromised [42]. During desiccation, the SOD and POD activity of G. biloba seed embryos were first reduced, then elevated to the highest value, before declining.…”
Section: Changes Of Sod and Pod Activity In G Biloba Seeds During Dementioning
confidence: 99%
“…Although phylogenetically closely related, these plants differ in their ecological requirements (Stevanović et al 1991) and ploidy levels (Š iljak-Yakovlev et al 2008). Protective systems involved in the response to dehydration/ rehydration, such as changes of membrane lipids (Quartacci et al 2002), ascorbate and glutathione contents (Sgherri et al 2004), antioxidative enzyme activities (Veljović-Jovanović et al 2006;Veljović-Jovanović et al 2008), have been investigated in R. serbica but not in R. nathaliae. The objective of this work was to analyse some oxidative/antioxidative events in leaves of R. nathaliae during dehydration and rehydration.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, polyphenol oxidase, which catalyzes the oxidation of mono-and o-diphenols to o-diquinones, showed increased protein abundance and enzyme activity in the dehydrating leaves of several resurrection species (Jiang et al, 2007;VeljovicJovanovic et al, 2008). Polyphenols are powerful detoxifiers of toxic ROS and may function as antioxidants during the first few hours of rehydration (Veljovic-Jovanovic et al, 2008). Although we begin to grasp how resurrection plants respond to desiccation or rehydration, without a relevant comparison between the responses of sensitive and tolerant tissues, any insight into the adaptive processes remains simply speculative.…”
Section: Introductionmentioning
confidence: 99%